Integrasi Nilai-nilai Al Islam dalam Mata Kuliah Fluida Melalui Model Pembelajaran Pemaknaan - Septi Budi Sartika; Ima Faizah (Universitas Muhammadiyah Sidoarjo, 2019)
The research aims to describe the implementation of fluid lectures in classrooms and laboratories on the integration of Al-Islam values through the Pemaknaan Learning Models, analyzing student learning outcomes, and describing Students' response in fluid lecturing through the Pemaknaan Learning Models. The study was conducted in 4 academic year students 2018/2019 a number of 18 students. The results showed that: 1) fluid lecturing in classes as well as in laboratories is carried out well, linking the concept of fluid to the values of Al-Islam; 2) Student learning results of the minimum B category; and 3) 88% of students respond positively to the fluid lecture by integrating Al-Islam's values through a learning model of use.